Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1523/jneurosci.0604-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated UPR and ERAD in Oligodendrocytes Maintain Myelin Thickness in Adults by Regulating Myelin Protein Translation

Abstract: Myelin proteins, which are produced in the endoplasmic reticulum (ER), are essential and necessary for maintaining myelin structure. The integrated unfold protein response (UPR) and ER-associated degradation (ERAD) are the primary ER quality control mechanism. The adaptor protein Sel1L (Suppressor/Enhancer of Lin-12-like) controls the stability of the E3 ubiquitin ligase Hrd1 (hydroxymethylglutaryl reductase degradation protein 1), and is necessary for the ERAD activity of the Sel1L-Hrd1 complex. Herein, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 64 publications
7
40
2
Order By: Relevance
“…Similar to these findings (Wu et al, 2020), another study showed that myelin thinning and behavioral inflexibility (touch screen based learning tasks) occurred without changes in axon number and diameter, confirming that myelin pathology precedes axonal pathology in demyelinating diseases (Silva et al, 2019). Although the PLP and Sel1L double knockout worsened the detrimental effects on myelin, a reduction of myelin basic protein (MBP) was also observed from 10 weeks of age, resulting in myelin thinning (Wu et al, 2020). Likewise, a previous study reported that abnormal distribution of MBP (rather than total MBP protein levels) contributes to myelin thinning (Silva et al, 2019).…”
Section: Myelin Thinning In Sel1l Deficient Mice Occurred Without Axosupporting
confidence: 89%
See 4 more Smart Citations
“…Similar to these findings (Wu et al, 2020), another study showed that myelin thinning and behavioral inflexibility (touch screen based learning tasks) occurred without changes in axon number and diameter, confirming that myelin pathology precedes axonal pathology in demyelinating diseases (Silva et al, 2019). Although the PLP and Sel1L double knockout worsened the detrimental effects on myelin, a reduction of myelin basic protein (MBP) was also observed from 10 weeks of age, resulting in myelin thinning (Wu et al, 2020). Likewise, a previous study reported that abnormal distribution of MBP (rather than total MBP protein levels) contributes to myelin thinning (Silva et al, 2019).…”
Section: Myelin Thinning In Sel1l Deficient Mice Occurred Without Axosupporting
confidence: 89%
“…However, astrocytes are believed to be less sensitive to UPR disruption (Murao and Nishitoh, 2017), although a recent study showed that the vesicular release of thrombin protease inhibitor from perinodal astrocytes is involved in myelin thinning (by preventing the attachment of myelin to axons) and in reduced conduction speed in optic nerves of mice (Dutta et al, 2018). Whether astrocytes were involved in microglia recruitment in this study (Wu et al, 2020) remains untested. However, the UPR is not unique to MS; rather it is a pathological hallmark of Alzheimer's, Parkinson's, and Prion diseases (García-González et al, 2018), suggesting that these neurodegenerative diseases share similar pathological pathways.…”
Section: Potential Involvement Of Microglia and Astrocytes In The Myementioning
confidence: 79%
See 3 more Smart Citations